2018
DOI: 10.1002/pbc.27234
|View full text |Cite
|
Sign up to set email alerts
|

Single‐agent bevacizumab in the treatment of recurrent or refractory pediatric low‐grade glioma: A single institutional experience

Abstract: Single-agent bevacizumab is efficacious in the management of recurrent or refractory pediatric LGG with radiographic and clinical responses similar to those reported for bevacizumab-based therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…This study showed a median survival of 9 months (17). In a recent study with the biggest number of cases in the literature, bevacizumab used as a single agent in the treatment of recurrent and refractory pediatric low grade glioma and showed 80% objective response rate (12 of 15 patients showed radiologic response) (18). In our case, a good treatment response with bevacizumab was seen in a SCA.…”
Section: Discussionsupporting
confidence: 56%
“…This study showed a median survival of 9 months (17). In a recent study with the biggest number of cases in the literature, bevacizumab used as a single agent in the treatment of recurrent and refractory pediatric low grade glioma and showed 80% objective response rate (12 of 15 patients showed radiologic response) (18). In our case, a good treatment response with bevacizumab was seen in a SCA.…”
Section: Discussionsupporting
confidence: 56%
“…No research has been done on the use of bevacizumab in ACP patients, but one small case series reviewed the use of bevacizumab in three patients with pilocytic astrocytoma (PA), another predominantly cystic tumor, and found that all three patients tolerated the therapy well and resulted in a decrease cyst volumes (22). Bevacizumab has also been shown recently to have clinical and radiographic effects in adult PA patients (23, 24) and has been shown to be a safe and tolerated therapy in pediatric patients with PA and other forms of low-grade glioma (25, 26). Overall, the patients presented tolerated therapy well without significant side effects or complications other than isolated Grade 3 neutropenia without associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Bevacizumab alone has also shown some efficacy in treatment of LGG. 11 Published trials of kinase inhibitors in pediatric LGG to date include investigations of sorafenib (a multikinase inhibitor), everolimus (an mTOR inhibitor), and selumetinib (a MEK inhibitor). [12][13][14] The phase II study of multikinase inhibitor sorafenib in patients with recurrent or progressive…”
mentioning
confidence: 99%